“Fertilización nitrogenada con diferentes densidades de siembra en el cultivo del maíz (zea mays L.)- variedad across, en condiciones de secado-bajo mayo, distrito de Juan Guerra- San Martín Perú” - Gonzales Trigozo, Ladi Leonor (2002)
The present investigation work was carried out in the experimental fields of the Experimental station The Future", located in the Km 14.5 of the highway Fernando Belaunde Terry South, district of Juan Guerra, County of San Martin and Region San Martin (Peru); located to a South latitude of 6º 35', geographically longitude of 76º 30' and toan altitude of 232 m.s.n.m. With the purpose of finding a good dose of nitrogen and an appropriate between density in the cultivation. of corn variety ACROSS it was carried out the experiment, being evaluated the effect of three fertilization levels Nitrogenum and three densities on the yield of the cultivation of the area of Bajo Mayo. The used nitrogen doses. were 130, 150 and 170 Kg/ha and the densities of seeded of 50000, 62500 and 70000 plants/he, being applied the nitrogen in two fractions, the first one to the 1 O days after the betw~en, and the second to the moment of the aporque. ·' The experimental design of Complete Blocks Randomized was used with factorial arrangement of 3 x 3 with three repetitions and 27 experimental units; and the results were analyzed by means of the variance analysis and the test of multiple ranges Duncan. The soil where it was C?rried out the experiment it was characterized to presenta loamy texture franc with good percentage of organic matter. The treatment T s with 70000 plants/he and 130 Kg of N/he reached the maximum yield with 5333 Kg/he in comparison to the treatment T8 with 62500 plants/ha and 170 Kg of N/he the one that obtained the smallest yield with 4400 Kg/he was. When making the economic analysis we observe that the treatment T 3 with 130 Kg of N/he and 70000 plants/ha that it occupied the first place in yield with 5333 Kg/he, is that is to say the treatment that showed bigger economic profitability, the treatment that it obtained bigger utility or economic benefit.